2012
DOI: 10.1021/nn204911k
|View full text |Cite
|
Sign up to set email alerts
|

Unusual, pH-Induced, Self-Assembly Of Sophorolipid Biosurfactants

Abstract: International audienceAn increasing need exists for simple, bioderived, nontoxic, and up-scalable compounds with stimuli-responsive properties. Acidic sophorolipids (SL) are glucose-based biosurfactants derived from the yeast broth of Candida bombicola (teleomorph: Starmerella bombicola). The specific design of this molecule, a sophorose head with a free end-COOH group at the end of the alkyl chain, makes it a potentially interesting pH-responsive compound. We have specifically investigated this assumption usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
153
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(165 citation statements)
references
References 58 publications
(145 reference statements)
12
153
0
Order By: Relevance
“…It was interesting to note that at basic pH, structure of an APG film seemed to be more densely packed (about 16 200 patches per mm 2 ) than at acidic pH (about 4000 patches per mm 2 at pH 4), but the overall surface organization was the same at all pH values. These two tests performed on control molecules confirmed that the evolution of sophorolipids self-assembly onto silicon wafer arises from the pH-dependence of self-assembly properties of this molecule, 56 and that these were not artifacts generated by possibly different wettability of silicon under different pH conditions.…”
Section: Effect Of Ph On Sophorolipid Surface Assemblymentioning
confidence: 58%
See 4 more Smart Citations
“…It was interesting to note that at basic pH, structure of an APG film seemed to be more densely packed (about 16 200 patches per mm 2 ) than at acidic pH (about 4000 patches per mm 2 at pH 4), but the overall surface organization was the same at all pH values. These two tests performed on control molecules confirmed that the evolution of sophorolipids self-assembly onto silicon wafer arises from the pH-dependence of self-assembly properties of this molecule, 56 and that these were not artifacts generated by possibly different wettability of silicon under different pH conditions.…”
Section: Effect Of Ph On Sophorolipid Surface Assemblymentioning
confidence: 58%
“…They have been recovered using method 1 as reported in a previous study by Baccile et al 65 Their purity has been evaluated at about 90% of both terminal and subterminal C18:1 congener and their equilibrium state in water is micellar as described earlier. 56,62,66 Sodium dodecyl sulfate (SDS) has been purchased from Aldrich and used as received. C10-Alkylpolyglycoside (APG, commercial name: Oramix) was provided by SEPPIC (France).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations